AC flashover performance for line post and pin post insulators in distribution 22 kV - W. Thipprasert (2018)
Electrical insulators in 22kV distribution system of the Provincial Electricity Authority (PEA) are mostly porcelain insulator types that consists of suspension, pin type, line post, and pin post insulators. The distribution lines will be polluted by industrial contaminants, salt fog or natural dust. Experience shows that pollution flashover is one of the main natural calamities harming and affecting the voltage stability and reliability of distribution system. This paper compares the test results obtained from artificial pollution tests according to IEC 60507 with line post type and pin post type insulators of medium system under same test conditions. The salt fog test results indicate that the pollution flashover performance of line post insulator is less than to 50 percent of wet power frequency withstand voltage at equivalent salt deposit density (ESDD) = 0.5 mg/cm2 and the leakage current (LC) of line post insulator increased to 10.2 mA at ESDD = 0.5 mg/cm2 at nominal voltage. In the experiment indicate that AC pollution flashover performance of pin post insulator has better than line post insulator in the serious pollution area. © 2012 IEEE.